CORN COBS AND RUMEN MICROBES FOR COMPLETE GOAT FEED: A ZERO-WASTE CASE STUDY FROM THE TANAH LAUT GOAT FARMERS ASSOCIATION - Ali, Muhammad Irvan; Hidayatulloh, Rifqi; Atmaja, Baluh Medyabrata; Bakti, Makmur Batara; Mecca, Rehad Edya; Santoso, Santoso; Rosidi, Maksum (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program addressed high feed costs and the underutilization of crop and slaughter by-products among goat-keeping households in Tanah Laut Regency, Indonesia, by introducing fermented complete feed made from corn cobs and hygienically processed bovine rumen digesta. The program aimed to strengthen farmer self-reliance while reducing open burning and the disposal of residues through a participatory action approach that iteratively combined co-design, hands-on training, on-farm application, evaluation, and refinement. Activities included orientation on feed management and waste-related issues, group mentoring on planning and record-keeping, practical production sessions using locally available inputs, and a thirty-day feeding trial on partner farms. Product quality was supported by simple process control and laboratory proximate analysis, which indicated a semi-dry fermented feed with moderate protein and high carbohydrate content, as is typical of upgraded crop residues. Goats readily consumed the feed, and farmers consistently reported improved appetite and palatability during the trial. Post-training surveys found that seventy-five percent of participants could independently reproduce the fermentation process and integrate it into routine management. Overall, the program demonstrated that converting corn cobs and rumen contents into fermented feed is feasible and acceptable at the farm level, supports skill adoption, and contributes to a zero-waste pathway. Follow-up monitoring will focus on batch consistency, spoilage prevention, feed intake, weight gain, and feed efficiency to document sustained impacts.Program pengabdian kepada masyarakat ini menanggapi tingginya biaya pakan dan belum termanfaatkannya limbah pertanian serta hasil samping rumah potong hewan di kalangan peternak kambing sekala rumah tangga di Kabupaten Tanah Laut, Indonesia, melalui penerapan pakan fermentasi berbahan tongkol jagung dan isi rumen sapi yang diproses secara higienis. Tujuan program adalah meningkatkan kemandirian peternak dalam penyediaan pakan, sekaligus mengurangi praktik pembakaran dan pembuangan limbah dengan mengubahnya menjadi pakan bernilai guna. Metode yang digunakan adalah partisipatif berbasis pemberdayaan yang dijalankan berulang melalui perancangan bersama, pelaksanaan, evaluasi, dan perbaikan. Kegiatan meliputi sosialisasi manajemen pakan dan isu lingkungan, pendampingan perencanaan serta pencatatan, pelatihan praktik produksi pakan fermentasi menggunakan bahan lokal, analisis proksimat produk, dan uji pemberian pakan selama tiga puluh hari pada peternakan mitra. Pakan hasil pelatihan dikonsumsi dengan baik oleh kambing dan peternak melaporkan peningkatan nafsu makan serta palatabilitas selama masa uji. Survei pascapelatihan menunjukkan bahwa tujuh puluh lima persen peserta mampu memproduksi kembali pakan fermentasi secara mandiri dan menerapkannya dalam manajemen rutin. Secara keseluruhan, program menunjukkan bahwa pemanfaatan tongkol jagung dan isi rumen sebagai pakan fermentasi layak diterapkan di tingkat peternak, memperkuat adopsi keterampilan, dan mendukung pendekatan zero-waste; pendampingan lanjutan akan diarahkan pada konsistensi mutu, pencegahan kerusakan, konsumsi pakan, pertambahan bobot, dan efisiensi biaya pakan untuk memastikan keberlanjutan dampak.